Romer-Romaner: Conn Iggulden, Emperor. The Gates of Rome. Harper and Collins Publishers, 2003; Valerio Massimo Manfredi, The Last Legion. Oversat fra italiensk, L’ultima legione. Pan Books, 2003 - Bülow-Jacobsen, Adam (AIGIS, 2024)
Intet.